Contemporary Theories of Civil Society in the Light of the Anthropocene - Pietrzak, Edyta B. (Sensus Historiae, 2022)
The idea of global civil society, which was popular at the turn of the 21st century, now seems to be an unattractive political project. Due to the subsequent economic, political or ecological crises, and the consequent ongoing radicalization of socio-political life, we have moved away from the global community in favour of transnational interests. However, is it not worth reconsidering it in the era of the Anthropocene? And maybe the categories of global responsibility and the common good do have the potential to be used? This article, which should be placed in sphere of political theory, discusses issues related to the local, global and transnational theories of citizenship and their hermeneutical interpretation with regards to discourses on the Anthropocene. The objective of this text is to verify the hypothesis that the factor prompting the organization of global civil society is civil disobedience, clearly favored and endowed with new life by the Anthropocene crisis. The methodological background for justifying the issues presented here is Hans George Gadamer’s hermeneutics.